Interest and Limits of [18F]ML-10 PET Imaging for Early Detection of Response to Conventional Chemotherapy - Jouberton, Elodie; Schmitt, Sébastien; Maisonial-Besset, Aurélie; Chautard, Emmanuel; Penault-Llorca, Frédérique; Cachin, Florent (Frontiers in Oncology, 2021)
One of the current challenges in oncology is to develop imaging tools to early detect the response to conventional chemotherapy and adjust treatment strategies when necessary. Several studies evaluating PET imaging with 2-deoxy-2-[18F]fluoro-D-glucose ([18F]FDG) as a predictive tool of therapeutic response highlighted its insufficient specificity and sensitivity. The [18F]FDG uptake reflects only tumor metabolic activity and not treatment-induced cell death, which seems to be relevant for therapeutic evaluation. Therefore, to evaluate this parameter in vivo, several cell death radiotracers have been developed in the last years. However, few of them have reached the clinical trials. This systematic review focuses on the use of [18F]ML-10 (2-(5-[18F]fluoropentyl)-2-methylmalonic acid) as radiotracer of apoptosis and especially as a measure of tumor response to treatment. A comprehensive literature review concerning the preclinical and clinical investigations conducted with [18F]ML-10 was perfomed. The abilities and applications of this radiotracer as well as its clinical relevance and limitations were discussed. Most studies highlighted a good ability of the radiotracer to target apoptotic cells. However, the increase in apoptosis during treatment did not correlate with the radiotracer tumoral uptake, even using more advanced image analysis (voxel-based analysis). [18F]ML-10 PET imaging does not meet current clinical expectations for early detection of the therapeutic response to conventional chemotherapy. This review has pointed out the challenges of applying various apoptosis imaging strategies in clinical trials, the current methodologies available for image analysis and the future of molecular imaging to assess this therapeutic response.